Social Entropy: An Information Measure of Institutional Complexity for Social Psychology - van Stokkum, Rebecca (Advances in Social Sciences Research Journal, 2024)
Information theory has impacted disciplines across science and technology, including the 20th century’s IT revolution. However, information theory has been applied much less to the social sciences and has not been applied at all to theoretical social psychology. While information-based statistical programs are used to analyze data across social disciplines, information theory has not been used to analyze social structure and the self as an informational process related to the conflict reducing characteristics of institutions. The present paper addresses this gap by suggesting Shannon information as a measure of the complexity within institutional settings in relation to the formally rationalizing drives of industrialized societies in contrast to the informal social control experienced in simpler societies. The paper analyzes social theory related to institutional complexity from several disciplines arguing that it is synonymous with information as suggested by Shannon. A post structural methodology for measurement of social complexity and directions for future research are suggested.